2015
DOI: 10.3402/fnr.v59.26488
|View full text |Cite
|
Sign up to set email alerts
|

Trends of fast food consumption among adolescent and young adult Saudi girls living in Riyadh

Abstract: BackgroundSaudi Arabia has passed through lifestyle changes toward unhealthy dietary patterns such as high fast food consumption. Adolescents and young adults, particularly girls, are the main groups exposed to and affected by these adverse eating behaviors.ObjectiveThe aim of this study was to examine the trends of fast food consumption among adolescent and young adult Saudi girls living in Riyadh, and to compare between them.DesignIn a cross-sectional survey, 127 adolescent Saudi girls (13–18 years) and 69 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
101
4
8

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(123 citation statements)
references
References 48 publications
10
101
4
8
Order By: Relevance
“…Moreover, within Saudi Arabia, fast food is generally available and easily accessible throughout the year through a wide variety of global fast food chains, especially in food courts of modern shopping malls (21). This could also explain our reported significant increase in fast food intake by expatriates during their residence in Saudi Arabia, which resembles that in the larger study (14) and the findings of prior Saudi and GCC studies (22,23). Moreover, previous studies have indicated that men consume more fast food than women do (24,25), which is in accordance with the findings of our study.…”
Section: Discussionsupporting
confidence: 78%
“…Moreover, within Saudi Arabia, fast food is generally available and easily accessible throughout the year through a wide variety of global fast food chains, especially in food courts of modern shopping malls (21). This could also explain our reported significant increase in fast food intake by expatriates during their residence in Saudi Arabia, which resembles that in the larger study (14) and the findings of prior Saudi and GCC studies (22,23). Moreover, previous studies have indicated that men consume more fast food than women do (24,25), which is in accordance with the findings of our study.…”
Section: Discussionsupporting
confidence: 78%
“…The results showed significant decrease in BMI for 49.5% of the participants. These changes was depending on number of visits, age and BMI at baseline (AlFaris et al, 2015). Similarly, the present study followed the same approach in applying multiple visits to follow up participants while they were going through out the intervention program.…”
Section: Discussionmentioning
confidence: 99%
“…Menurut penelitian di Riyadh menunjukkan bahwa fast food merupakan komponen penting pola makan remaja [2]. Menurut Asian Journal of Clinical Nutrition, Fast food banyak diminati remaja perempuan, sebesar 51,5% remaja perempuan lebih banyak mengkonsumsi fast food dibandingkan remaja laki-laki [3] .…”
Section: Pendahuluanunclassified
“…Menurut penelitian yang di lakukan di Iran menunjukkan bahwa fast food banyak dikonsumsi remaja yang berusia 15-19 tahun [4] . Konsumsi fast food banyak dilakukan remaja karena pada usia tersebut remaja mempunyai kesenangan pada makanan yang dianggap tren oleh teman sebaya [2] . Rata-rata uang saku yang didapat oleh responden adalah Rp.…”
Section: Hasil Dan Pembahasanunclassified
See 1 more Smart Citation